Analisis Tindak Tutur Representatif pada Video Tips Public Speaking dalam Kanal YouTube Sherly Annavita Rahmi - Wisnu Bima Prakoso; Yunanda Eka Novelianto; Jannatur Rohmah; Ayu Rahma Alfa Sania; Wenny Shafira Azzahra; Asep Purwo Yudi Utomo; Muhajir Muhajir; Yerry Mijianti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research analyzes representative speech acts in public speaking video tips on Sherly Annavita Rahmi's YouTube channel. There are two approaches in the research, namely methodological approach and theoretical approach. In the methodological approach, a qualitative descriptive approach is used, while in the theoretical approach, a pragmatic approach is used to analyze representative speech acts. The data collection technique in this study used free listening and note-taking techniques. The data that has been collected is analyzed using the commensurate method. Data presentation is done informally, besides that in this research also used presentation table to simplify and clarify the data analysis. A total of 109 representative speech acts were found with 7 types of representative speech acts namely stating, admitting, reporting, showing, mentioning, testifying, and speculating. The number of utterances found from 7 types of representative speech acts are 28 utterances of stating, 20 utterances of admitting, 9 utterances of reporting, 11 utterances of showing, 18 utterances of mentioning, 10 utterances of giving testimony, and 13 utterances of speculating. With this research, it is hoped that it can add insight for readers related to types of speech, especially representative speech acts.